Is there a cointegration relationshoip of long-term bond yield between US and Canada - Liu, Yuan (Université d'Ottawa | University of Ottawa, 2005)
As a small open-economy Canada's bond yields are said to be influenced by world financial markets, particularly the U.S. bonds market. As a result, I attempt to consider whether there is a close link between the Canadian and U.S financial markets. In this